Gender Influence on Pre-service Biology Teachers’ TPACK Profile - Mia Aina; Muhammad Erick Sanjaya; Muhammad Indar Pramudi; Aulia Sanova; Gusti Ayu Muthia (Jurnal Penelitian Pendidikan IPA, 2025)
TPACK research has been conducted on several subject teachers in schools in Jambi. However, research on prospective teachers, especially Biology, has not been widely conducted. What is new about this study is seeing the differences in TPACK results of female and male prospective teachers, which has not previously been done on prospective Biology teachers in Jambi. This research aims to examine the gap between two groups of male and female teacher candidates in assessing their TPACK knowledge. This study was conducted by distributing questionnaires to prospective teacher students using Google Form. There were 63 students consisting of 13 males and 50 females. The research method used was quantitative descriptive. The results showed that there were quite significant differences in TK and TCK indicators related to technology use. This is due to differences in training and time of technology use. Although male and female prospective teachers rated their domain knowledge very high, especially regarding CK, they rated their technological knowledge lower, including their ability to link this knowledge into TCK, TPK, and TPACK. This study has also produced recommendations for future research to improve TPACK of prospective biology teacher students